1992
DOI: 10.1021/jo00031a026
|View full text |Cite
|
Sign up to set email alerts
|

Rapid, high-yield synthesis of the marine sesquiterpenes debromoaplysin and aplysin via the acid-catalyzed rearrangement of a cyclobutachromanol

Abstract: reaction mixture was stirred at room temperature with a H2 balloon until the reaction was complete. After filtration, the filtrate was evaporated to give diol 13 (116 mg, 80%). The product was purified by bulb-to-bulb distillation (56-57 °C (0.1 Torr)):[a]D +10.5°(c 1.1, CHClg) (lit.14 [a]D +11.6°(c 2.12, CHC13);

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
2

Year Published

1999
1999
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 0 publications
0
17
0
2
Order By: Relevance
“…A unique example is the total synthesis of isocomene 59 by Pirrung [45] through Cargil rearrangement [46] of the cyclobutane derivative 58 (Scheme 31) obtained from intramolecular photocycloaddition of the dienone 57. The synthesis of 1-debromoaplysin by the group of Venkateswaran [47] is another classic example of the construction of five membered ring through acid catalyzed Wagner-Meerwein rearrangement of cyclobutyl carbinols 95 (Scheme 32). Tandem [2+2] photocycloadditions followed by ring fragmentation provides routes for constructing complex mediumsized ring skeletons.…”
Section: [2+2] Photocycloaddition In the Synthesis Of Structurally Comentioning
confidence: 99%
“…A unique example is the total synthesis of isocomene 59 by Pirrung [45] through Cargil rearrangement [46] of the cyclobutane derivative 58 (Scheme 31) obtained from intramolecular photocycloaddition of the dienone 57. The synthesis of 1-debromoaplysin by the group of Venkateswaran [47] is another classic example of the construction of five membered ring through acid catalyzed Wagner-Meerwein rearrangement of cyclobutyl carbinols 95 (Scheme 32). Tandem [2+2] photocycloadditions followed by ring fragmentation provides routes for constructing complex mediumsized ring skeletons.…”
Section: [2+2] Photocycloaddition In the Synthesis Of Structurally Comentioning
confidence: 99%
“…[344] Beispiele für die erstgenannte Sequenz finden sich in der Synthese von (À)-Hibaen [345] und in der formalen Totalsynthese von (AE )-Verrucarol. [346] Bei letzterem fand jedoch keine 1,2-Alkylwanderung statt, sondern das intermediär gebildete Kation [347] (AE )-Debromoaplysin und (AE )-Aplysin [348] oder (AE )-Trichodien (272). [349] [350] und (AE )-3-Oxosilphinen gezeigt.…”
Section: Sesquiterpens (Ae )-B-himachalen (263) (Abbildung 8)unclassified
“…Hanifin and Cohen reported the photoreactions of chromone with tetramethylethylene, 1-dimethoxyethylene, cyclopentene, and 2-butyne to obtain a variety of cycloadducts [17,18]. Nath et al employed the photocycloaddition reaction of 2, 3, 7-trimethylchromone with ethylene as a key reaction in the synthesis of two marine natural products [19]. Studies from Valiulin and Kutateladze showed that the Diels-Alder adducts of chromones could undergo an intramolecular [2p + 2p] alkene-arene photocyclization reaction [20].…”
Section: Introductionmentioning
confidence: 99%